STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING. (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI PERIODE 2016-2018). - Anindiya Mustika Gunarwati; Siti Maryam; Sudarwati Sudarwati (ITB AAS INDONESIA Surakarta, 2020)
The purpose of this study was to determine the effect of Capital Structure and Firm Size on Firm Value with Profitability as Intervening Variables. (Case Study on Manufacturing Companies in the Consumer Goods Industry Sector which are listed on the Indonesia Stock Exchange for the 2016-2018 Period). This research uses quantitative descriptive research type. Sample 27 companies using Purposive sampling technique. The analysis method uses path analysis with SPSS software version 21.Based on the test result min this study that the variable capital structure and company size have a positive and significant effect on profitability. Capital structure has no effect on firm value, firm size and profitability affect company value, and profitability is able to mediate the effect of capital structure and firm size on firm value. Keywords: capital structure, company size, profitability and firm value.